2000
DOI: 10.1001/archinte.160.16.2491
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Humanistic Outcomes in Patients With Gastroesophageal Reflux Disease Converted From Omeprazole to Lansoprazole

Abstract: After the PPI therapeutic interchange from omeprazole to lansoprazole, patients with GERD or heartburn previously stabilized while receiving omeprazole experienced more severe symptoms and expressed decreased patient satisfaction. These results suggest a need to monitor symptoms after similar interchange programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…It has been our anecdotal experience that with each antisecretory drug substitution program performed at our hospital (e.g., cimetidine to ranitidine, ranitidine to nizatidine, omeprazole to lansoprazole [LAN], LAN to rabeprazole [RAB]), some of our patients have complained that the new drug was less effective and have requested to be switched back. This experience is similar to that reported by other hospitals [4][5][6][7]. For example, at the Palo Alto VA hospital, approximately 10% of veterans who were switched from omeprazole to LAN were subsequently switched back.…”
Section: Introductionsupporting
confidence: 84%
“…It has been our anecdotal experience that with each antisecretory drug substitution program performed at our hospital (e.g., cimetidine to ranitidine, ranitidine to nizatidine, omeprazole to lansoprazole [LAN], LAN to rabeprazole [RAB]), some of our patients have complained that the new drug was less effective and have requested to be switched back. This experience is similar to that reported by other hospitals [4][5][6][7]. For example, at the Palo Alto VA hospital, approximately 10% of veterans who were switched from omeprazole to LAN were subsequently switched back.…”
Section: Introductionsupporting
confidence: 84%
“…17 Although some clinicians may challenge the clinical equivalence and therapeutic substitution of PPIs, [18][19][20][21] all drugs within this therapeutic category are known to be effective in both healing ulcerations and alleviating the symptoms of reflux. 22,23 The American Society of HealthSystem Pharmacists (ASHP) promulgated national guidelines for SUP in 1999.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…Research with 2 medications from a different class of drugs also with no significant differences in efficacy or safety found that about half of the patients converted from omeprazole to lansoprazole reported worsening symptoms of heartburn. 20 Nearly half of the subjects (47%) in our study who initiated conversion were successfully converted from sumatriptan to rizatriptan ODT. This result was accomplished without change in the number or cost of migraine-related office visits.…”
Section: Assessment Of Clinical Service and Cost Outcomes Of A Convmentioning
confidence: 80%